2017
DOI: 10.4239/wjd.v8.i4.143
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-mimetic compound hexaquis (benzylammonium) decavanadate is antilipolytic in human fat cells

Abstract: AIMTo assess in rodent and human adipocytes the antilipolytic capacity of hexaquis(benzylammonium) decavanadate (B6V10), previously shown to exert antidiabetic effects in rodent models, such as lowering free fatty acids (FFA) and glucose circulating levels.METHODSAdipose tissue (AT) samples were obtained after informed consent from overweight women undergoing plastic surgery. Comparison of the effects of B6V10 and reference antilipolytic agents (insulin, benzylamine, vanadate) on the lipolytic activity was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The obtained hypoglycemic effect of the investigated polyoxotungstates is in agreement with previously published in vivo studies that reported effective hypoglycemic actions of various types of polyoxotungstates on different diabetic animal models. [7][8][9] According to literature, a few putative mechanisms of POM induced normoglycemic action were indicated: a-glucosidase activity inhibition that consequently results in the reduced absorption of intestinal carbohydrates, 8 insulin mimetic effects including glucose uptake stimulation and lipolysis inhibition, 27 prevention of STZ-induced apoptosis of pancreatic b-cells, and stimulation of insulin synthesis. 7 Moreover, some polyoxotungstates were found to prevent the development of diabetic life-threatening microvascular and macrovascular complications by signicant limitation of aldose reductase activities and accumulation of advanced glycation end products.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained hypoglycemic effect of the investigated polyoxotungstates is in agreement with previously published in vivo studies that reported effective hypoglycemic actions of various types of polyoxotungstates on different diabetic animal models. [7][8][9] According to literature, a few putative mechanisms of POM induced normoglycemic action were indicated: a-glucosidase activity inhibition that consequently results in the reduced absorption of intestinal carbohydrates, 8 insulin mimetic effects including glucose uptake stimulation and lipolysis inhibition, 27 prevention of STZ-induced apoptosis of pancreatic b-cells, and stimulation of insulin synthesis. 7 Moreover, some polyoxotungstates were found to prevent the development of diabetic life-threatening microvascular and macrovascular complications by signicant limitation of aldose reductase activities and accumulation of advanced glycation end products.…”
Section: Discussionmentioning
confidence: 99%
“…The adipocyte preparations used in the present study were obtained from a total of 56 women of a mean age of 40 years with a mean body mass index (BMI) of 25. The fat cells were immediately subjected to hexose uptake assays as described below since freezing/thawing sequences are not compatible with the preparation of functional adipocytes, as described in [36].…”
Section: Methodsmentioning
confidence: 99%
“…Again, insulin did not significantly inhibit isoprenaline-stimulated lipolysis in this second set of experiments, that is, when tested at 100 nM against equivalent dose of isoprenaline (Figure 4). This is not so inconsistent, as human adipocytes are recognized as being less insulin-sensitive than rodent fat cells, especially in the case of overweight individuals [40]. Nevertheless, the presence of opipramol did not alter the antilipolytic effect of insulin-there was neither worsening nor addition of their effects when the two agents were tested simultaneously.…”
Section: Influence Of Opipramol On Basal and Stimulated Lipolytic Actmentioning
confidence: 99%